The Impact of Implementing Satellite-Based BTS in Indonesia’s 3T Regions on Digital Access and Community Social Life - Khalil Khalil; Miftahul Zanah (Jurnal Teknik Indonesia, 2026)
The construction of satellite-based Base Transceiver Stations (BTSs) in Indonesia's frontier, outermost, and disadvantaged (3T; terdepan, terluar, dan tertinggal) regions represents one of the government's key strategies for expanding internet connectivity. This study aims to analyze the impacts of satellite-based BTS implementation on education, the economy, public services, and social change. The study employed a qualitative case study approach using interviews, observations, and document analysis. The findings indicate that the deployment of satellite-based BTSs has had positive impacts, including improved access to digital education, healthcare services, communication, and online business opportunities. However, several challenges were also identified, including limited digital literacy, the spread of misinformation (hoaxes), increasing dependence on the internet, and changes in patterns of community social interaction. The findings demonstrate that the success of satellite-based BTS deployment in 3T regions depends not only on the availability of digital infrastructure but also on communities' readiness to use technology responsibly and effectively. The study further suggests that sustainable digital transformation in 3T regions requires simultaneous investment in digital literacy programs alongside physical infrastructure. Without such complementary initiatives, improved connectivity may inadvertently amplify social vulnerabilities, including exposure to misinformation and digital fraud, thereby widening rather than narrowing the digital divide. These findings underscore the need for policymakers to integrate community-based digital literacy initiatives, multi-stakeholder collaboration, and adaptive regulatory frameworks into Universal Service Obligation (USO) strategies to ensure that infrastructure investments produce equitable, inclusive, and resilient development outcomes.